Exploring key reaction sites and deep degradation mechanism of perfluorooctane sulfonate via peroxymonosulfate activation under electrocoagulation process. (1st December 2021) - Li, Meng; Mo, Ce-Hui; Luo, Xuan; He, Ke-Ying; Yan, Jian-Fang; Wu, Qiong; Yu, Peng-Fei; Han, Wei; Feng, Nai-Xian; YEUNG, King Lun; Zhou, Shao-Qi
Highlights: Fast decomposition of PFOS was achieved by electrocoagulation with PMS activation. Fe 2+ –OH is the key reaction site for producing ·OH during electrocoagulation process. ·OH play an important role in degrading PFOS. Degradation mechanism of PFOS can be clarified by DFT calculations. Abstract: Perfluorooctane sulfonate (PFOS), normally present in groundwater and surface water, is an emerging environmental contaminants, but is extremely difficult to be degraded due to high energy of the C-F bond. Here, an electrocoagulation (EC) technique coupled with peroxymonosulfate (PMS) activation was used to deeply degrade PFOS. Results showed that approximately 100% PFOS was removed from the solution in the monopolar serial (MS) mode within 60 min and achieved a high kinetic rate of 0.074 min −1, which was significantly higher than those of reported studies (Table S3). Energy consumption (2.06 kWh/kg) in the MS mode was significantly lower than that of Al (52.30 kWh/kg) and Zn (213.50 kWh/kg) electrodes, which further confirmed the potential application prospects of EC technique. The quenching experiments, electron spin response (ESR) analysis, and DFT calculations can verify that ·OH was the main radical from the reaction of Fe 2+ –OH reaction site with PMS. In addition, results from fluorine balance and TOC removal also indicated the complete mineralization and degradation of PFOS in the EC process. Quantum chemical calculations can confirm the PFOS degradation mechanism and key active sites for direct electron transfer and radical attack. After five cycle operations of PFOS degradation, the EC process was still effective in degrading PFOS with a removal efficiency above 98%. Thus, this work provided a novel alternative for the high-effective treatment of PFOS from contaminated environmental water bodies. Graphical abstract: Image, graphical abstract